The Cold Water Immersion and Cryotherapy in Post-Exercise Recovery: A Narrative - Stróżna, Katarzyna; Błażowska-Danielska, Olga; Jurewicz, Alicja; Gutowska, Oliwia; Nowak, Weronika; Kostuch, Wiktoria; Kowalewski, Łukasz; Naziri, Amir; Styczyńska, Maria; Chyl, Julianna (Quality in Sport, 2026)
Background. Post-exercise recovery is essential for athletic performance, training adaptation, and injury prevention. Cold water immersion (CWI) and whole-body cryotherapy (WBC) are widely used recovery strategies, yet uncertainty remains regarding their optimal application and long-term effects. Aim. To synthesise current evidence on the physiological mechanisms, recovery effects, and practical applications of CWI and WBC in athletic populations. Material and methods. A narrative review of studies indexed in PubMed/MEDLINE, Embase, SPORTDiscus, Web of Science, and the Cochrane Library was conducted. Original studies, systematic reviews, and meta-analyses published between 2009 and 2026 were analysed. Results. CWI (10–15 min, 10–15°C) consistently reduces delayed-onset muscle soreness (DOMS), lowers markers of muscle damage and inflammation, and improves perceived recovery. WBC (−110 to −190°C, 2–4 min) produces similar analgesic and anti-inflammatory effects and may offer greater practicality in some sporting settings. Both modalities can support short-term performance recovery during periods of intensive competition. However, repeated post-resistance exercise CWI may attenuate muscle protein synthesis and hypertrophic adaptations. Evidence regarding endurance adaptations is generally neutral and, in some cases, suggests potential benefits. Conclusions. CWI and WBC are effective tools for acute post-exercise recovery, particularly for reducing soreness and improving recovery perception. Their long-term use should be tailored to training goals, with caution advised during hypertrophy-focused resistance training phases. Further standardised, long-term studies are required.